1983
DOI: 10.1136/bmj.287.6403.1429
|View full text |Cite
|
Sign up to set email alerts
|

Relation between intake and plasma concentration of vitamin C in elderly women.

Abstract: The plasma concentration of vitamin C is relatively low in the elderly, particularly those in long stay hospitals,' but it is not clear to what extent these low concentrations are due to low intake. We examined the relation between intake and plasma concentrations of vitamin C in elderly women living at home and in long stay hospitals. Patients, methods, and resultsWe studied 101 elderly women: 24 were healthy and living at home (mean age 74), and 77 were long stay patients (mean age 83) in two geriatric hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…These findings, together with the evidence for the potential role of antioxidants such as vitamin C in preventing free radical damage (Frei et al 1989;Halliwell, 1994), provide considerable, although not conclusive, support for the idea that vitamin C intakes should be significantly higher than those preventing the development of clinical scurvy. Studies in healthy individuals have indicated that intakes above 60 mg/d, with averages around 100 mg/d, will saturate metabolic processes and maximize vitamin C content in white cells (Kallner et al 1979;Newton et al 1983;Levine et al 1996), and could, therefore, potentially maximize protection against diseases such as cancer, atherosclerosis and serious infections. Bates (1997) claims that, within the intake range for potential benefit, neither efficacy nor harm can be accurately gauged because there is insufficient evidence for either, in contrast to folate for the prevention of neural tube defects, where the evidence of benefit is overwhelming.…”
Section: -72mentioning
confidence: 99%
“…These findings, together with the evidence for the potential role of antioxidants such as vitamin C in preventing free radical damage (Frei et al 1989;Halliwell, 1994), provide considerable, although not conclusive, support for the idea that vitamin C intakes should be significantly higher than those preventing the development of clinical scurvy. Studies in healthy individuals have indicated that intakes above 60 mg/d, with averages around 100 mg/d, will saturate metabolic processes and maximize vitamin C content in white cells (Kallner et al 1979;Newton et al 1983;Levine et al 1996), and could, therefore, potentially maximize protection against diseases such as cancer, atherosclerosis and serious infections. Bates (1997) claims that, within the intake range for potential benefit, neither efficacy nor harm can be accurately gauged because there is insufficient evidence for either, in contrast to folate for the prevention of neural tube defects, where the evidence of benefit is overwhelming.…”
Section: -72mentioning
confidence: 99%
“…In their cross-sectional study of an elderly population of 138 males and 166 females on high vitamin C intakes, Garry et al [ 30 ] found that plasma vitamin C concentration increased rapidly up to a daily vitamin C dose of 150 mg, then the rate of increase slowed significantly. Newton et al [ 31 ] also reported a sigmodal relationship between plasma concentration of vitamin C and vitamin C intake in their study of 101 elderly women on lower vitamin C intakes. Jacob et al [ 20 ] also plotted plasma vitamin C concentration against the daily vitamin C dose, for an elderly population of 235 males and 442 females.…”
Section: Main Textmentioning
confidence: 96%
“… a mean of 7 patients, derived from Levine et al [ 32 ] b estimated from Fig. 5 and table and chart in Additional file 2 c converted from stated concentration of 1.0 mg/dL to SI units using formula provided by Newton et al [ 31 ]: 1.0 μmol/L ≈ 17.6 μg/100 mL …”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in healthy individuals have indicated that intakes above 60 mg/d, with averages around 100 mg/d, will saturate metabolic processes and maximize vitamin C content in white cells (Kallner et al 1979;Newton et al 1983;Levine et al 1996), and could, therefore, potentially maximize protection against diseases such as cancer, atherosclerosis and serious infections. Bates (1997) claims that, within the intake range for potential benefit, neither efficacy nor harm can be accurately gauged because there is insufficient evidence for either, in contrast to folate for the prevention of neural tube defects, where the evidence of benefit is overwhelming.…”
Section: Nutrition Discussion Forummentioning
confidence: 99%